Increased Benefit Generosity and the Impact on Workers' Compensation Claiming Behavior: An Interrupted Time Series Study in Victoria, Australia. Issue 3 (March 2019) - Lane, Tyler J.; Gray, Shannon E.; Sheehan, Luke; Collie, Alex
Abstract : Objective: To measure the effect of legislation in Victoria, Australia that increased workers' compensation benefits, including a raised wage replacement cap for higher earners, on claiming behaviors. Methods: Controlled interrupted time series of monthly claiming volumes and median disability duration, focusing on overall effects, impact among higher earners, and by condition type. Results: Overall claiming increased 12%, driven by back/neck (18%), and other musculoskeletal conditions (14%). Overall disability duration did not change, though increased 27% among back/neck conditions. Among higher earners, findings on claiming were mixed, while disability duration increased 33%, driven by back/neck musculoskeletal (MSK) conditions (23%). Findings for mental health conditions were mixed. Conclusions: The effect of benefit generosity on workers' compensation claiming and disability duration varied by earnings and condition. Effects were strongest among musculoskeletal conditions. Abstract : Supplemental Digital Content is available in the text